RDWG technique of determination of moisture content in Oil Palm Fruits - Abbas Z.; Mokhtar R.; Khalid K.; Hashim M.; Abdul Aziz S. (2023)
Both the reflection and transmission coefficients of oil palm fruits of various moisture contents have been measured using a rectangular dielectric waveguide (RDWG) technique in the frequency range between 8 GHz and 12 GHz. Good agreement between predicted and measured values of reflection coefficient suggests the potential of RDWG technique as a new, fast and accurate method for the determination of moisture content in oil palm fruits. 2007 EDP Sciences.